2010
DOI: 10.1210/en.2009-0541
|View full text |Cite
|
Sign up to set email alerts
|

The Kisspeptin/Neurokinin B/Dynorphin (KNDy) Cell Population of the Arcuate Nucleus: Sex Differences and Effects of Prenatal Testosterone in Sheep

Abstract: Recent work in sheep has identified a neuronal subpopulation in the arcuate nucleus that coexpresses kisspeptin, neurokinin B, and dynorphin (referred to here as KNDy cells) and that mediate the negative feedback influence of progesterone on GnRH secretion. We hypothesized that sex differences in progesterone negative feedback are due to sexual dimorphism of KNDy cells and compared neuropeptide and progesterone receptor immunoreactivity in this subpopulation between male and female sheep. In addition, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
215
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(232 citation statements)
references
References 43 publications
13
215
1
3
Order By: Relevance
“…Reduced P4 sensitivity was most dramatic within the ARN, with a nearly 60% decrease in PR-positive cells. This finding is in line with previous work showing decreased PR mRNA within the hypothalamus of PNA rats (32) and the ARN of PNA ewes (33). Although the mechanism of reduced PR expression remains to be determined, we can rule out reduced estrogen or P4 levels, as these remain unchanged in PNA mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Reduced P4 sensitivity was most dramatic within the ARN, with a nearly 60% decrease in PR-positive cells. This finding is in line with previous work showing decreased PR mRNA within the hypothalamus of PNA rats (32) and the ARN of PNA ewes (33). Although the mechanism of reduced PR expression remains to be determined, we can rule out reduced estrogen or P4 levels, as these remain unchanged in PNA mice.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, in the ewe, the ARN plays a major role in mediating P4 negative feedback to GnRH neurons (42), predominantly through dynorphin and kappa opioid receptor actions (43). Interestingly, the number of dynorphin, neurokinin B, and PR-positive cells are significantly reduced in the ARN of PNA ewes (33).…”
Section: Discussionmentioning
confidence: 99%
“…In another study of rats, DHT treatment had no effect on Kiss1 mRNA in the hypothalamus; however, it significantly elevated Kiss1 mRNA levels in pituitary tissue, ovary, and adipose tissue (Brown et al 2009). A study on female sheep found that prenatal androgen treatment resulted in a reduction by half of the number of NKB cells, whereas the number of kisspeptin cells remained at levels similar to those in the KNDy subpopulation of control females (Cheng et al 2010). The conflicting observations in these studies may result from differences between the action of DHT and testosterone, different neuron populations, species differences, and different age/sex groupings.…”
Section: Discussionmentioning
confidence: 96%
“…4 A-F), and Kiss1ra was shown previously to bind Kiss2, considered to be the more important form, with higher affinity than Kiss1 (32). In mammals there is strong evidence of sexual dimorphism of NKB neurons: larger numbers of NKB neurons have been identified in ARC of ewes than of rams (33). The transcription of NKB could be directly altered by estrogen receptors, as sequences corresponding to the estrogen responsive element and imperfect palindromic estrogen responsive element have been reported upstream of the TAC3 gene transcriptional start site (8).…”
Section: Pharmacological Analysis and Signal Transduction Pathways Ofmentioning
confidence: 91%